A vision problem in wire bonding - Mohd. Noor, Norliza; Mohd. Rijal, Omar; Mohd. Badar, Omar; P'ng, Yik Thon (2000)

(untitled)
A requirement for good wire bonding is the existence of intermetallics between the gold ball and bond pad. A digital image of the surface of the gold ball that was attached to the bond pad was obtained and analysed with MATLAB. The `counting method' (CM) is proposed for determining the percentage of intermetallics formation. Four experiments were performed to investigate the reliability of CM, the effect of light-offset, and the performance of a quality assistant (QA) in his ability to visually estimate (the visual method) the intermetallics coverage. The main results indicate that the visual method is inconsistent and less accurate than the counting method. The QA performs well for high intermetallics coverage, whilst for an approximately 50% intermetallics coverage the QA tends to overestimate. Critical remarks related to modeling the digital image are presented